RESISTANCE TO ANTIBIOTICS AND THEIR UTILIZATION BY MICROORGANISMS - Golub N.B.; Shi Xinhua; Levtun I.I. (Biotechnologia Acta, 2021)
With the development of antibiotics application, their spread in the natural environment increases dramatically. The presence of antibiotics in the environment changes microorganism and other living beings ratio and composition, which causes a negative impact on biochemical processes that take place in the environment. The spread of antibiotic resistance genes in environmental microorganisms is a growing problem of environmental safety and human health.